ANALISIS HUBUNGAN PUTARAN KATUP DENGAN KONSTANTA PEGAS DENGAN MENGGUNAKAN PEREDAMAN - Tsamroh, Dewi 'Izzatus; Jumiadi; David Ross (Universitas Islam Malang, 2023)
One of the problems of a machine is the vibration generated by the machine itself. Vibration is very influential on the structure and construction of the machine. One of the issues that is very important to note in these plans is the calculation of the deflection/deflection of the elements when subjected to a load. This is very important especially in terms of strength (strength) and stiffness (stiffness), where a horizontal bar that is loaded laterally will experience deflection. The deflection that occurs in elements that experience loading must be within an allowable limit. Based on the actual and theoretical research results for the Simple vibration apparatus, load and valve variations are directly proportional to the damping constant. The greater the load and valve rotation, the greater the damping constant. The beam deflection apparatus has several results, namely the load variation is directly proportional to the static deflection value. The greater the load, the greater the static deflection. Variation of distance (intermediate load point) is directly proportional to the static deflection value. The greater the distance, the greater the static deflection. Variation of distance (end load point) is directly proportional to the static deflection value. The greater the distance, the greater the static deflection. Thickness variation is inversely proportional to the static deflection value. The greater the thickness value, the smaller the static deflection. The width variation is inversely proportional to the static deflection value. The greater the width value, the smaller the static deflection.